Priorities in applied research to ensure programmatic success in the global elimination of canine rabies - Rupprecht, Charles E.; Kuzmin, Ivan V.; Yale, Gowri; Nagarajan, Thirumeni; Meslin, Francois-Xavier (Vaccine, 2019)
The elimination of human rabies mediated by dogs is attainable in concept, based upon current sensitive and specific diagnostic methods, existing safe and effective human and veterinary vaccines and a sound virological, pathological and epidemiological understanding of the disease. Globally, all developed countries achieved this goal. Regionally, major progress occurred throughout the Americas. However, less advancement is evident in Africa and Asia. Our objective was to concentrate upon those salient improvements to extant tools and methods over the next five years which could assist and simplify the task for both those developing countries that have already begun the process, as well as other localities in the earlier stages of consideration. We considered several categories of applied research which could be accomplished in the short term, based upon the available scientific evidence and recent recommendations from subject matter experts and key opinion leaders, focused upon perceived major limitations to prior program success. Areas of concentration included: laboratory-based surveillance, pathogen detection and characterization; human rabies prophylaxis; veterinary biologics; implementation of canine vaccination; and oral vaccination of free-ranging community dogs. Further real-time application in these core areas with proven techniques and technology would simplify attaining not only the global goal focused subtly upon human mortality, but the actual elimination of canine rabies as well.